Immunology of the Outer Membrane Proteins of Pasteurella Haemolytica A2, A7 and A9 in Sheep - Mohd Yusoff, Md Sabri (1999)

(untitled)
Pneumonic pasteurellosis is a common respiratory disease of goats and sheep throughout the world, including Malaysia. In Malaysia, Pasteurella haemolytica A2 is most commonly isolated from cases of pneumonic pasteurellosis in sheep and goats followed by Pasteurella haemolytica A7 and A9. Vaccination has been used widely to control the disease with uncertain success rate. The reasons for vaccination failure in the field were due to incompatible strains, unsuitable antigen as vaccine component and improper vaccination programme. Therefore, the attentions have been focused on the concept of a novel vaccine, which includes subunit vaccine. The outer membrane proteins (OMPs) of Pasteurella haemolytica A2, A7 and A9 have been extracted using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SOS-PAGE). Each serotype gave two to three major polypeptide bands with some minor bands. Immunoblotting, carried out using homologous and heterologous antisera against the OMPs from all serotypes. The results showed that the 30 kDa band of Pasteurella haemolytica A7 could be recognised by all antisera, and was thus concluded as the major and common immunogen. The in vivo tests using the OMPs of the three serotypes revealed that sheep injected with the 100/lg OMP followed by a booster dose on day 21 showed highest antibody level on day 28 post-injection. Animals vaccinated with the OMP of Pasteurella haemolytica A7 showed good immune response upon challenge with significantly (p<0.05) less severe lung lesions regardless whether challenged with Pasteurella haemolytica serotype A2, A7 or A9. Those animals vaccinated with the OMP of Pasteurella haemolytica A2 failed to protect against challenge with live Pasteurella haemolytica A9 while those vaccinated with the OMP of Pasteurella haemolytica A9 failed to protect against challenge with live Pasteurella haemolytiva A2 and A7. It is concluded that the OMP of Pasteurella haemolytica A7 provides cross-protection to challenges uSing live Pasteurella haemolytica A2, A7 and A9. Thus, the OMP of Pasteurella haemolytica A7, particularly the 30 kDa, could be the best candidate for a subunit vaccine against pneumonic pasteurellosis in sheep.